Characteristics of airborne fractal-like agglomerates of carbon nanotubes. (November 2015) - Wang, Jing; Bahk, Yeon Kyoung; Chen, Sheng-Chieh; Pui, David Y.H.
Abstract: Airborne carbon nanotubes (CNTs) pose a health threat at workplaces and play more and more important roles in toxicity studies, yet data and model on their detailed characteristics are lacking. Thus we investigated aerosolized multiwalled CNTs (MWCNTs) by tandem measurement of the mass and mobility size in order to characterize the MWCNT agglomerates. The results revealed a fractal-like relationship between the mass and mobility size in the range 50–500 nm indicating quite compact agglomerate structure, and an effective density in the range of 0.51–0.83 g/cm 3 . With the tube diameters and intrinsic density, the tube length in an agglomerate was determined reliably from the mass. We developed a model to compute the porosity and geometrical outer diameter of the agglomerates and derived the fractal relation between the mass and the outer diameter with a fractal dimension of 2.6, which agreed well with fractal dimensions of bulk CNT assemblies determined by other analytical methods. The effective density based on the outer diameter was in the range of 0.11–0.35 g/cm 3 and decreased with the increasing agglomerate size. Electron macroscopic images of the aerosolized MWCNTs provided comparable data for the outer diameter and fractal dimension.